The Effect of Profitability and Liquidity on Financial Distress Using the Altman Z-Score Method in Manufacturing Companies - Yohanes Pemandi Matan (INVOICE : JURNAL ILMU AKUNTANSI, 2022)
This research aimed to analize the impact of profitability and liquidity toward the financial district by using Altman Z-score method in manufacture industries which enrolled in Bursa Efek Indonesia period 2014-2016. The research population was the manufacture inductries which signed up in those period. There were 20 of manufacture industries as the sample and it  used the purpose sampling method based on predetermined criteria. The data taken from the annual finance report of Bursa Efek Indonesia.The analyzed method used multiple regression analysis, classical assumptions (normality test, heteroscedasticity test, multicollinearity test and autocorrelation test) and hypothesis testing using SSPS program. The findings showed the profitability (ration of Return on Aset and Return on Equity), and the liquidity (Cash Ration) had a positive significant to the industry financial distress